1958
DOI: 10.1017/s0021859600035097
|View full text |Cite
|
Sign up to set email alerts
|

The apparent digestibility of crude protein by non-ruminants and ruminants

Abstract: The apparent digestibility of crude protein by the non-ruminants, pigs, horses, rats, man and the rabbit, is shown to be related to the crude protein content of the feed, and the form of the relationship is similar to that for ruminants. With non-ruminants the apparent digestibility of crude protein is markedly depressed by the crude fibre content of the feed, whereas with ruminants the depression is only slight. The relevant equations show that pigs are much more sensitive to crude fibre than horses and rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1961
1961
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…As a result, by the end of the dry season, a random sample of animals of all ages and sexes showed that their diet contained only 2.18% crude protein. French, Glover & Duthie (1957) and Glover & Duthie (1958) have shown that the digestibility of crude protein is remarkably similar for ruminants in general and even for non-ruminants. Furthermore, from digestibility trials, P. Arman (personal communication) found that buffalo were very similar to cattle.…”
Section: The Qualit! Of Food In the Serengetimentioning
confidence: 99%
“…As a result, by the end of the dry season, a random sample of animals of all ages and sexes showed that their diet contained only 2.18% crude protein. French, Glover & Duthie (1957) and Glover & Duthie (1958) have shown that the digestibility of crude protein is remarkably similar for ruminants in general and even for non-ruminants. Furthermore, from digestibility trials, P. Arman (personal communication) found that buffalo were very similar to cattle.…”
Section: The Qualit! Of Food In the Serengetimentioning
confidence: 99%
“…Highly significant differences (P < .01) were noted in the ADC for DM, N, and E indicating that as the Solka Floe portion of the diet increased, the animals became less efficient in utilizing their feed. An inverse relationship between level of fiber in the diet and the ADC of organic nutrients has been reported by several workers (Teague and Hanson, 195^;Lloyd and Crampton, 1955;Whiting and Bezeau, 1957a;Glover and Duthie, 1958;Likuski, Bowland and Berg, 1961 ;Pond, Lowrey and Maner, 1962;Boenker e;t a2., 19^9;Bowland e^ aJ., 1970;Keys, Van Soest and Young, 1970).…”
Section: Amentioning
confidence: 69%
“…Using this information the rumen contents of buffalo were divided into the two components leaf+leaf sheath (I), and stem (s) and the ratio of their residence times R/Ts was taken to be 1/1.3. The justification for extrapolating from cattle to buffalo comes from Glover & Duthie (1958) who showed that the process of digestion in different species of ruminants was very similar.…”
Section: (K:)mentioning
confidence: 99%